Altered Neuromagnetic Activity in Persistent Postural-Perceptual Dizziness: A Multifrequency Magnetoencephalography Study - Jiang, Weiwei; Sun, Jintao; Xiang, Jing; Sun, Yulei; Tang, Lu; Zhang, Ke; Chen, Qiqi; Wang, Xiaoshan (Frontiers in Human Neuroscience, 2022)
Objective: The aim of our study was to investigate abnormal changes in brain activity in patients with persistent postural-perceptual dizziness (PPPD) using magnetoencephalography (MEG). Methods: MEG recordings from 18 PPPD patients and 18 healthy controls were analyzed to determine the source of brain activity in seven frequency ranges using accumulated source imaging (ASI). Results: Our study showed that abnormal changes in the temporal-parietal junction (TPJ) were observed at 1-4 Hz, 4-8 Hz, and 12-30 Hz in PPPD patients compared with healthy controls, and changes in the frontal cortex were found at 1-4 Hz, 80-250 Hz, and 250-500 Hz in PPPD patients compared with controls. There was no significant difference in source strength between the PPPD and control groups. Conclusion: Our results demonstrated that alterations in the TPJ and frontal cortex may play a critical role in the pathophysiological mechanism of PPPD and that frequency-dependent changes in brain activity were also involved in the pathophysiology of PPPD.